El pez arco iris al rescate! - Pfister, Marcus; Gutiérrez, Guillermo (New York : Ediciones Norte-Sur ; Distributed in the U.S. by North-South Books, 1996)
Although his friends want to ignore the new striped fish in their midst, Rainbow Fish must decide whether to help him when a shark attacks.
Accelerated Reader
Keywords: Fishes -- Juvenile fiction; Sharks -- Juvenile fiction; Friendship -- Juvenile fiction; Peces -- Novela juvenil; Tiburones -- Novela juvenil; Amistad -- Novela juvenil